Developing and Validating a 4D Reflection Rubric for Assessing Teacher Professional Reflection in Narrative Writing - Lilis Ernawati; Ribut Wahyu Eriyanti; Masduki; Siti Agustin; Apriani Riyanti (Women, Education, and Social Welfare, 2026)
Assessing teacher reflection in narrative texts remains challenging because existing rubrics often privilege explicit analytical writing and may overlook reflective meanings embedded in stories. This study aimed to develop and validate a multidimensional, genre-sensitive 4D Reflection Rubric for assessing pedagogical reflection in teacher-authored short stories. Using a Research and Development design adapted from the 4D model, the study involved 30 in-service elementary school teachers who produced classroom-based narratives, five expert validators, and five independent raters. The rubric was developed across four dimensions: cognitive, affective-relational, ethical, and action-oriented reflection. Data were analyzed using the Content Validity Ratio, Aiken’s V, Intraclass Correlation Coefficient, and descriptive statistics. The findings showed that nine of twelve indicators achieved full expert agreement, while three indicators required refinement. All indicators demonstrated satisfactory clarity, with Aiken’s V values ranging from 0.80 to 0.93. The rubric also showed excellent inter-rater reliability, with an ICC value of 0.90. Ethical reflection emerged as the most prominent dimension, followed by action-oriented and affective-relational reflection, whereas cognitive reflection was less explicitly articulated. These findings indicate that the 4D Reflection Rubric is valid, reliable, and responsive to both explicit and implicit forms of teacher reflection. This study contributes a genre-sensitive assessment tool for strengthening teacher professional development, feedback quality, and institutional capacity building in educational settings.